A Content Analysis of Media Information Exposure on Tourism Destination Image - Laba, I Nengah (Journal of Business on Hospitality and Tourism, 2018)
This study examines the issue of the formation of destination image through the analysis of the specific tourism discourse. It is the linguistic variety of English used in tourism which was written by tourists on websites imaging the destination of the Campuhan Ridge. The study focuses on the way tourism discourse contributes to convey an image of a destination using the approach of media exposure theory. Referring to previous scientific studies, tourism destination image have been shaped through the mediation between tourists’ mental constructs and web-based tourism discourse. Using a theory of information media exposure and an approach of linguistic study, samples of texts from websites were examined and analyzed using qualitative content analysis. Results show that linguistic features seen from lexical and phrasal choices were used together with functional attributes, psychological attributes, Psychological-holistic impressions, and Common-Unique dimension when tourists describing about tourism destination image.